‘It's Like a Sentence Before the Sentence' — Exploring the Pains and Possibilities of Waiting for Imprisonment - Laursen, Julie (The British journal of criminology, 2020)
This article explores the implications of the ‘imprisonment queue' in Norway. Based on interview data (N = 200), we show that while interviewees waiting to serve their sentences enjoy certain benefits such as being able to prepare for or negotiate the terms of their imprisonment, they also suffer from uncertainty and powerlessness. The suspension of their lives while they wait hinders them in pursuing their ground projects, things that really matter to them. This peculiar phenomenon has not received attention from prison scholars generally, as well as scholars writing on Nordic Exceptionalism specifically. This article addresses that gap and poses questions about the relative mildness of the short Norwegian sentences, and more broadly, about what constitutes punishment.